Asymptotic Expression of Eigenvalues for a Class of Fractional Boundary Value Problems (Journal of Nonlinear Modeling and Analysis, 2024)
Based on the properties of Mittag-Leffler function, the behaviorof eigenvalue and the eigenfunction for a class of fractional differential equations with integral boundary value condition is discussed, and the asymptoticexpression of the eigenfunction is given.
Keywords: Fractional differential equation; boundary value problem; eigenvalue; eigenfunction; asymptotic estimation.